Profil Macronutrient Content of Lingula unguis as an Antistunting Candidate - Minsas, Sukal (Jurnal Biologi Tropis, 2024)
The diversity of marine biota is very high, with nutritional and chemical content that can be used to fulfill food requirements and maintain health. Stunting is a national health problem that has a big impact on the nation's future, so it is necessary to look for local food sources that have the potential to be used in dealing with stunting. The aim of this research is to obtain nutritious food from the sea, which has the potential to be a source of protein and fat and is very necessary for children during their growth and development period, pregnant and breastfeeding mothers. One of these food sources is Lingula unguis which has empirically been used as a side dish by the coastal communities of Mutiara Beach. The results of measuring the macronutrient content of marine biota Lingula unguis show a water content of 75.3%, ash content of 1.12%, protein content of 3.3%, fat content of 2.07% and carbohydrate content using difference calculations obtained at 18.35%. The protein and fat macronutrient content of L. unguis can be a consideration for use in the consumption menu for treating stunting.